A8.10 Human memory t cells from the bone marrow are resting and maintain long-lasting memory. (31st January 2014) - Okhrimenko, Anna; Grün, Joachim R.; Westendorf, Kerstin; Fang, Zhuo; Reinke, Simon; von Roth, Philipp; Wassilew, Georgi; Kühl, Anja A.; Kudernatsch, Robert; Demski, Sonya; Scheibenbogen, Carmen; Tokoyoda, Koji; et al.
Abstract : Objectives: Memory T cells are essential components of immunological memory, but little is known about their maintenance. Recirculating memory T cells of blood and secondary lymphoid organs slowly decay in numbers. In mice, we have recently identified professional resting memory CD4 + T cells located in the BM and stably maintained in dedicated survival niches. The cells are resting, despite expression of CD69. Here we analyse and compare paired human peripheral blood (PB) and BM samples for phenotype, specificity and cytokine profiles of memory CD4 + and CD8 + T cells. Material and Methods: Mononuclear cells were isolated from paired PB and BM samples from individuals undergoing hip replacement surgery. Phenotypic analysis and cytokine profile of memory T-cells in response to CMV pp65, tetanus toxoid and measles were measured by flow cytometry. Proliferation and cell cycle status were analysed using Ki-67 and propidium iodide staining, respectively. Global transcription of cells was assessed by microarray analysis. Results: Significantly higher numbers of memory T cells were found in BM than in PB. BM memory T cells displayed polyfunctionality, secreted a multitude of cytokines, and specificities for all recall antigens tested. They maintained long-lasting memory, even when it was not detectable in blood. CD69-expressing memory T cells were detected in BM but not in PB. Ki-67- and propidium iodide-positive cells were significantly lower in CD69 + memory T cells from BM compared to PB. BM CD69 + memory T cells showed a resting global gene expression profile. Conclusions: BM is home to resting, professional memory CD4 + and CD8 + T cells, providing systemic, stable longterm memory.